2019
DOI: 10.1111/petr.13591
|View full text |Cite
|
Sign up to set email alerts
|

High depression rates among pediatric renal replacement therapy patients: A cross‐sectional study

Abstract: Depression is common in pediatric chronic kidney disease (CKD) patients. Depression is associated with inferior long‐term outcomes. There is a paucity of studies that evaluate depression and possible associated factors in children and adolescents requiring renal replacement therapy (RRT). Cross‐sectional study using Children`s Depression Inventory in a cohort from a large urban center. Forty‐seven pediatric RRT patients (26 female, 12 peritoneal dialysis (PD), 17 hemodialysis (HD), 18 after successful kidney t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…These include cognitive deficits, learning disabilities, memory deficits, low self-esteem, poor self-body image due to short stature, high-risk behavior, anxiety, and depression, with the prevalence of depression reportedly as high as 10%–35%. [ 23 24 25 ] They not only have a lower intellectual and academic functioning compared to healthy peers, but also have poor social functioning which interferes with their coping skills. [ 26 27 ] Nonadherence is another primary concern, especially involving transplant recipients at the time of transfer and generally in all patients less than 25 years of age.…”
Section: Hct Process: Stakeholder Roles and Challenges Encounteredmentioning
confidence: 99%
“…These include cognitive deficits, learning disabilities, memory deficits, low self-esteem, poor self-body image due to short stature, high-risk behavior, anxiety, and depression, with the prevalence of depression reportedly as high as 10%–35%. [ 23 24 25 ] They not only have a lower intellectual and academic functioning compared to healthy peers, but also have poor social functioning which interferes with their coping skills. [ 26 27 ] Nonadherence is another primary concern, especially involving transplant recipients at the time of transfer and generally in all patients less than 25 years of age.…”
Section: Hct Process: Stakeholder Roles and Challenges Encounteredmentioning
confidence: 99%
“…Anxiety and depression are highly prevalent among pediatric CKD patients and often are associated with a history of maternal depression and anxiety, sometimes even during pregnancy for prenatally diagnosed conditions [22]. Mood disorders can affect as many as 2/3 of patients, especially in families with lower socioeconomic status [22].…”
Section: Chronic Kidney Disease/end-stage Kidney Disease In Adolescents and Young Adultsmentioning
confidence: 99%
“…Anxiety and depression are highly prevalent among pediatric CKD patients and often are associated with a history of maternal depression and anxiety, sometimes even during pregnancy for prenatally diagnosed conditions [22]. Mood disorders can affect as many as 2/3 of patients, especially in families with lower socioeconomic status [22]. In the CKD cohort, >25% of the patients have internalizing problems, attention problems and poor adaptive skills, persistent hypertension-associated attention problems, and resulting behavioral symptoms [23].…”
Section: Chronic Kidney Disease/end-stage Kidney Disease In Adolescents and Young Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of depression have been reported in 25% to 56% of Mexican adult patients on dialysis [7,[27][28][29]. Similarly, moderate to severe symptoms of depression have been found in Mexican children and adolescents on RRT [30]. The study of resilience in the renal population has shown that the construct is present in various dimensions in the life of the patient and has a mediating effect in relation to other psychological and contextual variables [21,23].…”
Section: Introductionmentioning
confidence: 99%